Morbidity and mortality during wars and armed conflicts: trends and patterns - Yu.O. Sukhov (Civic Union "Communicable Diseases Intensive Care Association", 2022)
Wars cause an increase in morbidity that occurs not only during but also after war due to damage to medical infrastructure, water and food systems, transportation infrastructure, and power grids. It is known that the incidence of coronary heart disease, arterial hypertension, cerebrovascular and endocrine diseases, mental disorders increases during armed conflicts. Unhealthy lifestyle, as well as lack of physical activity and anxiety-depressive disorders contribute to increased cardiovascular risk in wartime. A separate problem is the health of internally displaced persons, who have higher rates of morbidity and mortality compared to the national average. Accurate data on morbidity and mortality in Ukraine are currently unavailable. A significant part of the morbidity and mortality of Ukrainian civilians during the war is caused by the forced displacement of the population, the unavailability of medical care, and the lack of adequate supply of water and food, the deterioration of the material and financial support of most citizens. These same reasons, combined with the increase in population density, the deterioration of hygienic measures and the violation of immunization campaigns, contribute to the spread of infectious diseases, primarily diarrheal (cholera) and respiratory (measles, COVID-19, tuberculosis). The impact of the war in Ukraine on the health of the population is being actively studied, which will allow to determine the leading trends of this impact and create a plan for the restoration of full-fledged medical care.